Species composition of the mammal fauna in the Phuquoc national park, Kiengiang province - Dang, Nguyen Xuan; Phuong, Dang Huy (Academia Journal of Biology, 2014)
Two mammal surveys were conducted in September 2004 and January 2005 in the Phuquoc national park, Kiengiang province. Based on the survey results and literature reviews, a list of 43 mammal species belonging to 18 families and 6 orders was compiled. Among these recorded species, 6 species are listed in the Red Data Book of Vietnam (2000), 6 species in the 2005 IUCN Red list and 11 species in the Governmental Decree 32/2006/ND-CP. Silvered langur (Semnopithecus germaini), slow loris (Nycticebus coucang), pygmy loris (Nycticebus pygmaeus), crab-eating macaque (Macaca fascicularis), stump-tailed macaque (Macaca arctoides), small-clawed otter (Aonyx cinerea) and fruit bats (Pteropus spp.) are species of the most conservation concern. The contruction of infrastructural facilities (roads, houses) and the tourism development pose great challenges for the biodiversity conservation in the Park.